Pengaruh Kemampuan Kerja dan Motivasi Tenaga Kerja Suplier Terhadap Kualitas Pelayanan Konsumen - Fransisca Natalia Natalia (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
This study aims to analyze Effect of Job Skills and Work Motivation to Quality of Service. This research was conducted at PT. Akur Pratama/TOSERBA YOGYA CIKAMPEK focused on labor supplier in the fashion area with a population of about 100 labor supplier and sample 80 respondents drawn at random sampling. The hypothesis was built to examine the influence of several variables and test them on 80 employees at PT AKUR PRATAMA / TOSERBA YOGYA Cab. Cikampek. The population in this study were all suppliers of labor guards at TOSERBA YOGYA Cab. Cikampek, and the number of samples is 80 respondents. The results of this study can be seen that the magnitude of the effect simultaneously between work ability and work motivation on service quality of 0.455, while the joint contribution to known at 0.207 or 20.7% while the remaining 18, 7% is influenced by other variables. The results of this study can be seen that there is a significant correlation between the variables of work ability and work motivation on service quality. Variable work ability and work motivation have an influence together with service quality.The results showed that the Job Skills and Work Motivation effect on Quality of Service. So, if PT. Akur Pratama/TOSERBA YOGYA CIKAMPEK want to increase Quality of Service should first improve Job Skill and Work Motivation.